Effect of Umbilical Cord Entanglement and Position on Pregnancy Outcomes - Natsuko Kobayashi; Shigeru Aoki; Mari S. Oba; Tsuneo Takahashi; Fumiki Hirahara (Hindawi Limited, 2015)
Introduction. To investigate the effect of complex umbilical cord entanglement primarily around the trunk on pregnancy outcomes. Methods. We studied 6307 pregnant women with singleton pregnancies who underwent vaginal delivery of an infant at ≥37 weeks of gestation. Cases were classified into no cord, nuchal cord, and body cord groups and defined as cases without umbilical cord entanglement, one or more loops of the umbilical cord around the neck only, and umbilical cord around the trunk only, respectively. Pregnancy outcomes were compared among these three groups. Results. The no cord, nuchal cord, and body cord group included 4733, 1451, and 123 pregnancies, respectively. Although delivery mode was not significantly different among the three groups, 1-minute Apgar scores <7 and umbilical artery (UA) pH <7.10 were significantly more common in the umbilical cord entanglement groups than in the no cord group. In particular, the frequency of 5-minute Apgar scores <7 was significantly higher (P=0.004), whereas that of UA pH <7.10 tended to be higher (P=0.057) in the body cord group than in the nuchal cord group. Conclusion. Compared to nuchal cord, umbilical cord entanglement around the trunk was associated with a higher risk of low Apgar scores and low UA pH.